PENGEMBANGAN APLIKASI NASKAH DINAS ELEKTRONIK PADA BAG TIK KORLANTAS POLRI (Universitas Methodist Indonesia, 2022)
This study aims to create a system that can recap the state of correspondence in the form of a desktop-based application that can manage correspondence management quickly, accurately, relevantly and effectively. This correspondence management administration system is designed using the SDLC (Software Development Life Cycle) method, as a software development method and built using Netbeans IDE 8.2 software which uses the Java programming language and MySQL as its database. This research produces an administrative system that can help the admin personnel of the ICT Korlantas Polri in managing mail data in a fast and efficient time. And with this application, it is hoped that it will help work activities that require accurate information and be able to minimize human errors that often occur in the data collection process for correspondence management when using a manual system.